2011
DOI: 10.1177/1099800411414698
|View full text |Cite
|
Sign up to set email alerts
|

A Rodent Model to Advance the Field Treatment of Crush Muscle Injury During Earthquakes and Other Natural Disasters

Abstract: Approximately 170 earthquakes of 6.0 or higher magnitude occur annually worldwide. Victims often suffer crush muscle injuries involving impaired blood flow to the affected muscle and damage to the muscle fiber membrane. Current rescue efforts are directed toward preventing acute kidney injury (AKI), which develops upon extrication and muscle reperfusion. But field-usable, muscle-specific interventions may promote muscle regeneration and prevent or minimize the pathologic changes of reperfusion. Although curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Crushing-induced injury is performed through applying a clamp or dropping a mass on a superficial muscle (Speck et al, 2013, Takagi et al, 2011. As a result of crushing injury, collagen fibers accumulate around the myofiber bundles (Filippin et al, 2011) with increased levels of TGF-β1 and insulin-like growth factor (IGF-I) (Takagi et al, 2011, Zimowska et al, 2009.…”
Section: Traumatic-induced Modelsmentioning
confidence: 99%
“…Crushing-induced injury is performed through applying a clamp or dropping a mass on a superficial muscle (Speck et al, 2013, Takagi et al, 2011. As a result of crushing injury, collagen fibers accumulate around the myofiber bundles (Filippin et al, 2011) with increased levels of TGF-β1 and insulin-like growth factor (IGF-I) (Takagi et al, 2011, Zimowska et al, 2009.…”
Section: Traumatic-induced Modelsmentioning
confidence: 99%
“…1,2 In general, the early stage of pathophysiologic progression of muscle crush injury includes ischemia, necrosis, inflammation, reperfusion, and in the later stages, regeneration. [3][4][5] Estrogen is a key hormone that influences muscle tissue and is active in healthy and injured muscle, including both the early and later stages.…”
Section: Introductionmentioning
confidence: 99%
“…[17,[30][31][32][33] It was presently understood that a closed, piston-activated compression model most accurately mimicked factors causing crush trauma in earthquakes. [20][21][22] In animal experiments with ischemia-reperfusion models, it was shown that disruption of circulation in the extremities increased muscle damage. After removal of pressure on the extremity, myoglobin-containing oxidative ferrous derivatives that may cause cell injury, hemoglobin, lactic acid, potassium, and creatinine are released during the reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot mechanical crushing procedure was performed on 2 rats in order to ensure that it could be performed effectively, similar to the rodent model of Kirsten Speck et al [22] After In order to prevent slippage of the crushing device piston, as well as skin maceration, the gastrocnemius regions were wrapped loosely with 1 fold of 5-cm plaster without harming circulation, creating a surface area.…”
Section: Pilot Studymentioning
confidence: 99%